My year of rest and relaxation - Moshfegh, Ottessa 1981- (Vintage, 2021)
This is the story of a woman with no name. Young, thin, pretty, a recent Columbia graduate, she lives in an apartment on the Upper East Side of Manhattan paid for, like everything else, by her inheritance. Yet she longs to lose herself completely. It's the year 2000 in a city aglitter with wealth and possibility; what could be so terribly wrong? My Year of Rest and Relaxation is a savagely funny novel of a woman looking out from the abyss